HIV-associated Lipodystrophy Syndrome: A Review of Clinical Aspects - Jean-Guy Baril; Patrice Junod; Roger LeBlanc; Harold Dion; Rachel Therrien; François Laplante; Julian Falutz; Pierre Côté; Marie-Nicole Hébert; Richard Lalonde; Normand Lapointe; Dominic Lévesque; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Approximately two years after the introduction of highly active antiretroviral therapy for the treatment of HIV infection, body shape changes and metabolic abnormalities were increasingly observed. Initially, these were ascribed to protease inhibitors, but it is now clear that nucleoside reverse transcriptase inhibitors also contribute to lipodystrophy syndrome. The syndrome groups together clinical conditions describing changes in body fat distribution that include lipoatrophy, lipoaccumulation or both. However, there does not appear to be a direct link between lipoatrophy and lipoaccumulation that would support a single mechanism for the redistribution of body fat. Currently, there is no clear definition of lipodystrophy, which explains the difficulty in determining its prevalence and etiology. There are no current guidelines for the treatment of fat distribution abnormalities that occur in the absence of other metabolic complications. The present article reviews the current state of knowledge of the definition, symptoms, risk factors, pathogenesis, diagnosis and treatment of the morphological changes associated with lipodystrophy syndrome.